2010
DOI: 10.1016/j.jneumeth.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Regional convection-enhanced delivery of gadolinium-labeled albumin in the rat hippocampus in vivo

Abstract: Convection-enhanced delivery (CED) has emerged as a promising method of targeted drug-delivery for treating central nervous system (CNS) disorders, but the influence of brain structure on infusate distribution is unclear. We have utilized this approach to study extracellular transport and distribution of a contrast agent in the hippocampus, a complex structure susceptible to CNS disorders. The magnetic resonance (MR) contrast agent diethylene triamene penta-acetic acid chelated gadoliniumlabeled albumin (Gd-al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 53 publications
(56 reference statements)
6
41
0
Order By: Relevance
“…Our data for distribution of locally delivered Gd-DTPA in soft tissue are consistent with in vivo tissue delivery measured by Adams et al [1], Nelson et al [22], and Owen et al [24]; with MRI data for drug distribution from a local infusion in vitro by Raghavan et al [26]; and with the local distribution after infusion into brain tissue in vivo [4] (Table 2). Our data showing visualization of Gd-DTPA over time with an MRI are consistent with Astary et al [4] and Raghavan et al [26], who also showed that gadolinium distribution can be seen to change with time.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data for distribution of locally delivered Gd-DTPA in soft tissue are consistent with in vivo tissue delivery measured by Adams et al [1], Nelson et al [22], and Owen et al [24]; with MRI data for drug distribution from a local infusion in vitro by Raghavan et al [26]; and with the local distribution after infusion into brain tissue in vivo [4] (Table 2). Our data showing visualization of Gd-DTPA over time with an MRI are consistent with Astary et al [4] and Raghavan et al [26], who also showed that gadolinium distribution can be seen to change with time.…”
Section: Discussionsupporting
confidence: 90%
“…Failures in treatment are often attributed to inadequate débridement; however, it is not possible to know if adequate antimicrobial levels are achieved throughout the postdébridement wound in these failures. Clinically used delivery vehicles include acrylic bone cement (PMMA) and CaSO 4 , although many other vehicles, including collagen, have been investigated. Antimicrobial release from these vehicles ranges in vitro from 100% of contained antimicrobial over 24 hours for collagen [17] to 3-5% over 1 month for low-porosity PMMA [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is valid when the infusion rate is low and pressure during infusion in tissue is small, or if the initial deformation occurs over a much shorter time scale than CED infusion time. Perivascular transport was not accounted for in this CED model, but has been sometimes observed in infusion into the rat hippocampus [16]. In porous media, the continuity of fluid equation is…”
Section: Porous Mediamentioning
confidence: 99%
“…Connected fissures are a set of smaller fluid-filled spaces between tissue borders that can provide another low resistance pathway for interstitial fluid and infusate diversion. During CED, infusate may leak into fissures, and this phenomena has been observed following CED infusion into dorsal and ventral hippocampi [16,17], as well as at other CED infusion sites [2,18]. To the best of our knowledge, previous computational brain transport and CED models have not accounted for the impact of these fissures on drug delivery.…”
Section: Introductionmentioning
confidence: 99%